The ways of friendship : anthropological perspectives - Desai, Amit, 1977-; Killick, Evan (Berghahn Books, 2010)
Friendship is an essential part of human experience, involving ideas of love and morality as well as material and pragmatic concerns. Making and having friends is a central aspect of everyday life in all human societies. Yet friendship is often considered of secondary significance in comparison to domains such as kinship, economics and politics. How important are friends in different cultural contexts? What would a study of society viewed through the lens of friendship look like? Does friendship affect the shape of society as much as society moulds friendship? Drawing on long-term ethnographic fieldwork in Asia, the Middle East, Africa, Latin America and Europe, this volume offers answers to these questions and examines the ideology and practice of friendship as it is embedded in wider social contexts and transformations.